The Influence of Socioeconomic Environment on the Social Interaction Skills of Early Childhood Aged 5–6 Years - Nur Asyari Qomariyah Asyari; Wulan Patria Saroinsong; Aprilia Dey Dias Wardini (Journal of Art and Creativity in Early Childhood Education, 2025)
This study aims to determine the influence of the socio-economic environment on the social interaction of early childhood aged 5-6 years. Early childhood is considered a golden period for development, where social interaction plays a crucial role in shaping character and social skills. The socio-economic environment including parents educational background, family income, and access to social facilities is believed to significantly influence children’s patterns of social interaction. This research employed a quantitative approach using the ex post facto method. Data were collected through closed ended Likert scale questionnaires distributed to 230 parents of children aged 5-6 years in the Ampel Sub-district, Surabaya. The research instruments were tasted for validity dan reliability. Data analysis techniques included Pearson correlation and simple linear regression using IBM SPSS 25. The results showed a significant relationship between the socio-economic environment and children’s social interaction. The higher the family’s socio economic condition, the better the child’s ability to engage in social interaction. This study provides practical contributions for parents, early childhood educators, and educational institutions in designing inclusive learning strategies and policies that take family socio-economic factors into account.